Pengaruh Tingkat Pengetahuan, Kepercayaan dan Reputasi Lembaga terhadap Minat Membayar Zakat Melalui Mobile Banking : Studi Kasus Nasabah BSI Kabupaten Bogor - Dwi Jayanti Mandasari; Abrista Devi; Suyud Arif (IAI Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effect of the level of knowledge, trust and reputation of the institution on the intention to pay zakat through BSI mobile. The population used in this research is the people of Bogor district, the research sample is 100 respondents. The method used in this study is a quantitative approach method, and uses the SEM (structural equation modeling) data analysis method with the PLS (partial least square) approach which is processed using the Smart PLS 4 application. The results show that the trust and reputation variables of the institution have a significant influence. significant effect on the intention to pay zakat while the level of knowledge has no significant effect. Simultaneously the variable level of knowledge, trust and institutional reputation has a influence of 42% on the intention to pay zakat, hile the remaining 58% is influenced by other variables not examined in this study.